Analisis Pengaruh Risiko Kredit Terhadap Profitabilitas Bank Syariah Sumatera Utara - Tri Auri Yanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
The application of risk management in Islamic banks is very important which aims to identify, measure, monitor, and control risks arising from all business activities of the Bank that have the potential for losses due to certain events, including credit risk due to debtor failure, credit concentration risk, counterparty credit risk, and settlement risk. Financial ratios or Financial Ratios are a company's financial analysis tool to assess the performance of a company based on comparison of financial data contained in the financial statement post (balance sheet, profit / loss statement, cash flow statement) which is an alternative to test whether financial ratios are useful for making predictions about future profitability. CAR, NPF and FDR are measures of the ability to predict profitability. The data was obtained from the OJK Sharia Banking Statistics publication report. The independent variables in this study are Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) while Return on Assets (ROA) as the dependent variable. Data collection methods in this study are documentation and literature. During this period, the research data were normally distributed. This study shows that variables, CAR, FDR and NPF influence ROA.